OPTIMIZING THE VOLUME OF BUDGET SUBSIDIES ALLOCATED TO HIGHER EDUCATION INSTITUTIONS (International Congress on Economics, Management and Business Studies, 2026)
In modern economic conditions, the issue of financing the higher education system is one of the priority directions of state policy. Optimizing the volume of budget subsidies allocated to higher education institutions is of great importance not only for ensuring the rational use of financial resources, but also for enhancing the quality and competitiveness of education.
Keywords: higher education institutions are over-financed, while others are not provided with sufficient funds